THE RISE OF BYD IN INDONESIA: HUMAN CAPITAL, INNOVATION, AND MARKETING AGILITY AS COMPETITIVE ADVANTAGES - Hasta Asymar Herlan; Yandri Ahmad Rifandi; Budhi Haryadi; Yuni Siswantoro (Jurnal Comparative: Ekonomi dan Bisnis, 2026)
The global automotive industry is undergoing a profound transformation driven by the shift from internal combustion engine (ICE) vehicles to electric vehicles (EVs), intensifying competition among global manufacturers. This study examines the rise of BYD in the global and Indonesian EV markets through strategic human capital, technological innovation, and marketing agility, with emphasis on the role of human resource capabilities. Using a qualitative inductive approach based on secondary data, evidence is synthesized from annual reports, industry databases, and credible media sources. Findings show that BYD’s rapid growth is strongly supported by strategic human capital expansion, intensive R&D talent development, and continuous capability upgrading, which enable technological innovation and market responsiveness. In Indonesia, BYD achieved rapid market penetration and significant EV market share shortly after entry. The study concludes that competitive advantage in the EV industry is driven by integrated strategic capabilities. It is recommended that future research incorporates primary data for deeper managerial insights. The study is limited by reliance on secondary data and lack of firm-level interviews.